Integritas dalam Peribadatan Menurut Amos 4:4-5 - Yanti, Maria Evvy (Sekolah Tinggi Teologi Sumatera Utara, 2020)
Because of its nature Amos 4:4-5 as a part of 4:1-13 has been interpreted in many ways. Often it is linked to the holy places with sins of people. This kind of interpretation is problematic. First, while emphasizing the essence of worship in Amos 4:4-5, it has different situation. Second, this text contains many ideas, content and compilation. It shows a reading of Amos 4:4-5 in social historical as a setting. It also considers theological consequences of such a reading. The result of this research show the essence of worship in Amos 4:4-5 to develop the people characters and faith to God in developing their meaning life. AbstrakTeks Amos 4:4-5 sebagai bagian dari Amos 4:1-13 menimbulkan beberapa penafsiran.Dari beberapa penafsiran terdapat kecenderungan untuk mengaitkannya dengan tindakan kejahatandi tempat-tempat ibadah. Penafsiran ini problematis. Pertama, dengan menekankan pada esensiibadah dalam Amos 4:4-5 dalam situasi teks yang berbeda. Kedua, teks-teks ini terdiri dari beberapaide, isi dan penggabungan-penggabungan. Tulisan ini memperlihatkan sebuah pembacaan teks Amos4:4-5 dalam setting sejarah social. Juga mempertimbangkan konsekuensi teologisnya. Hasil daripenelitian menekankan bahwa pemaknaan ibadah merupakan pembentukan karakter dan keimanankepada Allah untuk mengembangkan kehidupan yang bermakna.